Accessing Possible Selves With Limited College Knowledge: Case Studies of Latino Boys in Two Urban Continuation Schools. (September 2022) - Huerta, Adrian H.
Justice-involved youth are less likely to hold positive attitudes toward education and education systems due to the unfair treatment that they experience. Despite the exchange of college knowledge between justice-involved Latino young men in urban continuation schools, this topic is relatively absent from college access and higher education literature. UsingOyserman and Markus's (1990a) notion of possible selves as a theoretical framework and drawing from in-depth interviews and observations with 26 middle and high school Latino young men across two urban continuation schools, I find that educators intentionally did not share college knowledge with Latino young men. Furthermore, I reveal that these youth possess inaccurate information about the college admissions process. If schools are to help the most vulnerable student populations prepare and aspire for postsecondary education, it is important to equitably disseminate accurate college knowledge to all students.